Isolated shoulder weakness as a result of a cortical infarction in the precentral gyrus - Pouya Entezami; John A. Hopper (Greater Baltimore Medical Center, 2015)
Since its discovery, our understanding of the primary motor cortex has continued to evolve. The presentations of rare, isolated, motor palsies of small muscle groups have heavily contributed to the characterization of the somatotopic representation of the human body on the cortex. We present a case of localized, left shoulder small muscle group weakness secondary to ischemic cerebral infarction in the primary motor cortex. The patient experienced full recovery over several days. Strokes causing isolated shoulder weakness are rare due to the relatively small area dedicated to shoulder motor function in the precentral gyrus. However, our patient presented with a larger area of infarction than in previously reported cases, demonstrating the large individual variability that may exist within the motor cortex somatotopic map.